A new selective inhibitor for IMP-1 metallo-β-lactamase, 3Z, 5E-octa-3, 5-diene-1, 3, 4-tricarboxylic acid-3, 4-anhydride. (15th January 2023) - Ikeda, Akari; Ikegaya, Yoshiki; Honsho, Masako; Matsui, Hidehito; Nonaka, Kenichi; Ishii, Takahiro; Asami, Yukihiro; Hanaki, Hideaki; Hirose, Tomoyasu; Sunazuka, Toshiaki
Graphical abstracts: Highlights: 3 Z, 5 E -Octa-3, 5-diene-1, 3, 4-tricarboxylic acid-3, 4-anhydride (ODTAA) was found by a selective IMP-1 MBL inhibitory activity from microbial metabolites. First total synthetic route was established by Suzuki-Miyaura cross-coupling reaction, Julia- Kocienski olefination, and singlet oxygen oxidation. The introduction of catechol improved the antimicrobial activity against IMP-1 MBL-producing E. coli and P. aeruginosa . β-Carbonyl-α, β-unsaturated carboxylic acid was suggested as a pharmacophore for selective IMP-1 MBL inhibitory activity. Abstract: 3 Z, 5 E -Octa-3, 5-diene-1, 3, 4-tricarboxylic acid-3, 4-anhydride (ODTAA, 1 ) was isolated from Paecilomyces sp. FKI-6801 for its selective IMP-1 MBL inhibitory activity. The first total synthesis of 1 from the commercially available compound was achieved in 9 steps with 28% overall yield. Introduction of catechol to the maleic anhydride of 1 improved the IC50 toward IMP-1 MBL and the inhibitory activity against IMP-1 MBL-producing P. aeruginosa . Treatment of the maleic anhydride scaffold with amine showed that the β-carbonyl-α, β-unsaturated carboxylic acid moiety is required as a pharmacophore for IMP-1 MBL inhibition.